Japan : - Etherton, P. T. (Jarrolds, limited, 1933)
This book introduce about Britain of the East, the menace of numbers, a "five year plan" for Japan, coal and iron - the facts, how rich is Japan, Japan prepares, Japanese foreign policy examined...